Continuous Assessment in the Saudi Education System: Challenges and Opportunities - Aldawood, Saad Fahad (Journal of Humanities & Social Sciences, 2021)
Nowadays, there are many methods for evaluating institutional performance in accordance with the productivity and outcomes of learners, teachers and administrators. The utilization of continuous assessment in the Saudi education system has always been characterized as a way for facilitating and monitoring students’ learning based on the teaching practices within organizations. This paper sheds new light on the current challenges associated with the utilization of continuous assessment in Saudi education system. It is a state-of-the-art review of the development of general education in Saudi Arabia and discusses in details the concept of continuous assessment. The review is established with addressing potential opportunities of a successful utilization of continuous assessment method in the Saudi education system. In conclusion, it was found out that many essential principles regarding the proper utilization of continuous assessment must be considered and acknowledged by teachers during the utilization of continuous assessment in their classroom practices such as fully understanding the achievement targets of continuous assessment at the initial stage of teaching process, modulating the form and content of continuous assessment to make its objectives more achievable, and conducting a proper preparation program and planning of continuous assessment procedures and activities in the classroom.
Keywords: tests; Education System Evaluation; Continuous Assessment; Institutional Development; Testing